1993
DOI: 10.3109/00207459309024114
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differencesm in the Eeg During Cognitive Activity

Abstract: EEG activity of 16 adult volunteers. 8 male and 8 females was monopolarly recorded at P3 and P4 at rest and during solution of three series of tasks: one analytic, one spatial and one mixed demanding both kinds of processing. The following main effects were observed: Men showed significantly higher beta relative power than women, while women showed significantly higher alpha relative power than men during all conditions. Alpha relative power decreased, while theta relative power increased during tasks solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 34 publications
4
33
0
1
Order By: Relevance
“…Next, women tend to exhibit greater overall EEG alpha power than men both during baseline measures and during performance of different types of tasks (Benninger et al, 1984;Gasser et al, 1988;Matsuura et al, 1985). Such findings have been replicated in studies dealing with mental rotation task, where patterns of greater EEG alpha power among women have been reported both during a baseline condition and while performing mental rotation tasks (Arce, Ramos, Guevara, & Corsi-Cabrera, 1995;Corsi-Cabrera et al, 1993;Roberts & Bell, 2000b). Finally, there is no indication of a sex difference in the alpha band in children between 6 years of age and 11-12 years of age (Benninger et al, 1984;Matsuura et al, 1985;Roberts & Bell, 200b).…”
Section: Eeg Age and Sex Interactionsmentioning
confidence: 67%
See 1 more Smart Citation
“…Next, women tend to exhibit greater overall EEG alpha power than men both during baseline measures and during performance of different types of tasks (Benninger et al, 1984;Gasser et al, 1988;Matsuura et al, 1985). Such findings have been replicated in studies dealing with mental rotation task, where patterns of greater EEG alpha power among women have been reported both during a baseline condition and while performing mental rotation tasks (Arce, Ramos, Guevara, & Corsi-Cabrera, 1995;Corsi-Cabrera et al, 1993;Roberts & Bell, 2000b). Finally, there is no indication of a sex difference in the alpha band in children between 6 years of age and 11-12 years of age (Benninger et al, 1984;Matsuura et al, 1985;Roberts & Bell, 200b).…”
Section: Eeg Age and Sex Interactionsmentioning
confidence: 67%
“…Results of greater right parietal alpha suppression by high ability males during spatial tasks were replicated by Berfield, Ray, and Newcombe (1986), who likewise found no consistent relations among either high or low ability females and right or left alpha suppression during the spatial tasks. In another study, Corsi-Cabrera, Ramos, Guevara, Arce, & Gutierrez, (1993) found alpha suppression for males, but not for females, during a spatial task. These EEG data suggest that males and females have electrophysiological differences in their processing of spatial material.…”
Section: Sex Differencesmentioning
confidence: 86%
“…Those studies found that women and men showed different EEG activity under various conditions [32][33][34]. Radulescu and Mujica-Parodi [35] stated that women have a better olfactory sensation than men in many species and differences in their sensitivity may be based on biological meanings.…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects were found only for male participants. Females showed no effect of observation, model skill level, or training schedule on the acquisition of Space There is a large body of literature that addresses gender differences on such factors as cognitive abilities (Cochran & Wheatley, 1989;Gordon & Kravetz, 1991), spatial abilities (Law, Pellegrino, & Hunt, 1993;Maccoby & Jacklin, 1974), learning styles (Philbin, Meier, Huffman, & Boverie, 1995), and brain activity (Corsi-Cabrera, Ramos, Guevara, Arce, & Gutierrez, 1993), to name only a few. Whether gender differences are due to biology or socialization processes has not yet been established, since these are not easily manipulated (Jacklin,198 9).…”
Section: -8mentioning
confidence: 99%